2016
DOI: 10.1161/circimaging.116.004731
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging of Cardiac Strain Pattern Following Transplantation of Human Tissue Engineered Heart Muscles

Abstract: Background The use of tissue engineering approaches in combination with exogenously produced cardiomyocytes offers the potential to restore contractile function after myocardial injury. However, current techniques assessing changes in global cardiac performance following such treatments are plagued by relatively low detection ability. As the treatment is locally performed, this detection could be improved by myocardial strain imaging that measures regional contractility. Methods and Results Tissue engineered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 34 publications
(39 reference statements)
0
23
0
Order By: Relevance
“…Human embryonic stem cell line WA07 (H7) and cardiomyocyte differentiation using small molecules were based on protocols described in previous studies [25] . Before labeling, hESC-CMs were dissociated and re-seeded into a new Matrigel-coated plate to form a single monolayer of cells.…”
Section: Methodsmentioning
confidence: 99%
“…Human embryonic stem cell line WA07 (H7) and cardiomyocyte differentiation using small molecules were based on protocols described in previous studies [25] . Before labeling, hESC-CMs were dissociated and re-seeded into a new Matrigel-coated plate to form a single monolayer of cells.…”
Section: Methodsmentioning
confidence: 99%
“…With the advent of human pluripotent stem cells (hPSC), including human embryonic stem cells (hESC) and human induced pluripotent stem cells (hiPSC), the availability of large-scale production in bioreactors and differentiation/purification protocols, sufficient quantities of essentially pure human cardiomyocytes can be produced according to GMP requirements and applied in the engineering of heart muscle. 19 Human EHM rings and patches [19][20][21] as well as human engineered heart tissue strips 22 from human embryonic (hESC)-and hiPSC-derived cardiomyocytes could be implanted and used to partially repair large muscle defects in rat and guinea-pig hearts. These studies collectively demonstrated long-term cardiomyocyte retention (>200 days), maturation, graft vascularization, and a variable degree of proliferation; further electrical coupling to the host myocardium was observed in some, but not all investigated guinea-pigs, 22 in line with earlier studies demonstrating the isolation of human engineered muscle xenograft grafts by scar formation in athymic rats.…”
Section: Cells and Their Requirements For Te-directed Remuscularizationmentioning
confidence: 99%
“…T1 mapping sequences are not standardized, making measurements difficult to reproduce or interpret across institutions [52]. A final set of techniques, tagging and feature tracking MRI, are reproducible and quantitative, but only indirectly measure collagen or other ECM biology [55]. Tagging and feature tracking measure the mechanical deformation (strain) of the myocardium, which is affected by the collagen structure [52].…”
Section: Organ-scale Imagingmentioning
confidence: 99%